Notes On the Intervention with Men Who Use Violence Against Intimates - Favell, Andrew M (PINS-Psychology in Society, 2026)
This article privileges the conception of violence as a political process that organises, shapes and arranges both intimate as well as social relationships. The specific form of arrangement produced by violence resonates with a "fascist"-type of organisation. Adopting such a perspective, the perpetrator of violence is understood to participate in the circulation and invigoration of particular discursive possibilities as ways through which he comes-into-being with others. The question of responsibility therefore shifts to address his participation in such forms of social negotiation and arrangement and the specific product that such participation engenders. A process of intervention with perpetrators is discussed from this perspective.